NOVEL ALISYA KARYA MUHAMMAD MAKHDLORI: SEBUAH TELAAH STRUKTURAL - Basuki Sarwo Edi (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
The purpose of this study is to describe the intrinsic elements of Alisya novel by Muhammad Makhdloril. The problem that will be examined and studied is how to describe the intrinsic elements that are the base of a literary work, among other things, the existence of themes, and mandates, figures and characterizations, plots, and settings that become the structure of Muhammad Makhdori's Alisya novel? The method used is descriptive method. The advantages of research is that it can reveal the structure of a novel that can be used as a material for studying learning to deal with life problems. The source used in this research is Alisya novel by Muhammad Makhdlori. The results obtained in this study indicate that the Alisya novel by Muhammad Makhdori has the theme of poverty can make people go berserk and invites immorality. Life needs to struggle and work hard.